Preparation, characterization and optimization of empty fruit bunch nanocrystalline cellulose (ncc) by acid hydroysis - Nor Atikah Binti Ab Rahman (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Empty fruit bunch is one of the most abundant lignocellulosic wastes and has a potential in producing nanocellulose for various uses. In this study, an alkaline pre-treatment and acid hydrolysis are the most important process were utilized for the production of nanocrystalline cellulose, NCC. At first stage, EFB powder was first treated with 4 wt% sodium hydroxide (NaOH) solution at 80 C at 2 hours. The treated EFB fibres then was bleached with 1.7 wt% sodium chlorite (NaClO2) solution, acetate buffer and distilled water at 70 C-80 C for 2 hours following with acid hydrolysis. At his stages, clear milky solution produced was introduced as Nanocrystalline cellulose. The optimization has been carried out by using Box-Behnken under RSM to analyze the effect of acid concentration, reaction temperature and reaction time on production of NCC yields. From the model response, the optimum NCCs yield produced is 17.52%. While, the optimum condition acid concentration, reaction temperature and reaction time were at 64.81%w/w, 60 p0sC and 43.03min respectively. Through this experiment, nanocrystalline cellulose are successfully produced by acid hydrolysis.